2021
DOI: 10.1111/adb.13097
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic inhibition of corticostriatal circuits reduces cued reinstatement of methamphetamine seeking

Abstract: Methamphetamine (meth) causes enduring changes within the medial prefrontal cortex (mPFC) and the nucleus accumbens (NA). Projections from the mPFC to the NA have a distinct dorsal‐ventral distribution, with the prelimbic (PL) mPFC projecting to the NAcore, and the infralimbic (IL) mPFC projecting to the NAshell. Inhibition of these circuits has opposing effects on cocaine relapse. Inhibition of PL‐NAcore reduces cued reinstatement of cocaine seeking and IL‐NAshell inhibition reinstates cocaine seeking. Meth, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
(129 reference statements)
3
11
0
Order By: Relevance
“…13,29 However, we have shown that male and female rats both respond robustly for meth-associated cues. 27,29 Consistently, we did not find evidence of sex differences in behavioural relapse testing or MMP activity, and thus, data are collapsed across both sexes. The means and standard errors are desegregated by sex in Table 1.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…13,29 However, we have shown that male and female rats both respond robustly for meth-associated cues. 27,29 Consistently, we did not find evidence of sex differences in behavioural relapse testing or MMP activity, and thus, data are collapsed across both sexes. The means and standard errors are desegregated by sex in Table 1.…”
Section: Discussionsupporting
confidence: 74%
“…29,32,33 However, sex differences are not always detected, which can be accounted for by variations in session length, drug dose, or fixed ratio value. 27,34,35 In the current study, we used a 6-h protocol for 15 days of meth self-administration for both sexes, and although we found sex differences in active lever responding during drug self-administration, it was males, not females, that pressed the active lever more. This finding replicates our previous study using the same meth regimen.…”
Section: Sex Differencesmentioning
confidence: 70%
See 2 more Smart Citations
“…Taken together, these studies support the conclusion that hypoactivity in infralimbic to nucleus accumbens shell neurons promotes Toluene reward-associated behaviors. Finally, such a dichotomy is clearly drug-dependent as cue-induced heroin seeking ( Rogers et al, 2008 ), morphine-induced conditioned place preference ( Hearing et al, 2016 ), and cue-induced methamphetamine seeking ( Kearns et al, 2022 ) all require activity in either the infralimbic cortex and/or its specific projection to the nucleus accumbens shell.…”
Section: Discussionmentioning
confidence: 99%